The biomechanical properties of an epithelial tissue determine the location of its vasculature - Martin Kragl (Nature Portfolio, 2016)
Vasculature is denser in soft than in stiff tissues. Kragl et al. suggest a mechanistic link between biomechanical tissue properties and vascularization by showing that integrin-linked kinase reduces the contractile forces of the cell cortex in endocrine pancreatic cells, facilitating their adhesion to blood vessels and enabling pancreatic islet vascularization.